Quality of Service in the Preparation of Population and Civil Registration Administration Documents at the Cirebon Regency Population and Civil Registration Office - Puspita Ningrum, Setia Devi; Yuliyanti, Feni; Permana, Ipik; Haryo Bharoto, R. Mahendra (Asian Journal of Social and Humanities, 2024)
Public Service Procurement is a task for the government in creating community welfare, for the creation of welfare in the community it is necessary to have quality in the implementation of these services, in this era of digitalization the government is expected to be able to implement technological advances by utilizing digitalization as an effort to improve services with easy access for the community. This study is aimed at finding out how the quality in the implementation of public services at the Cirebon Regency Population and Civil Registration Office, measuring the level of public satisfaction with the Cirebon Regency Population and Civil Registration Office, and finding out how to Improve the Quality of Public Services at the Cirebon Regency Population and Civil Registration Office. The research method used is a Qualitative Research Method with Questionnaire data collection techniques that are disseminated to the community in Cirebon Regency through Google Forms, Interviews with employees of the Cirebon Regency Population and Civil Registration Office, and Location Observation which is a place of service located at the Cirebon Regency Population and Civil Registration Office. Research shows that the quality of administrative document loading services at the Cirebon Regency Population and Civil Registration Office has not been maximized, improvements are needed to improve the quality of service. a) improving Facilities and Infrastructure that are Facilities in the Service process; b) hard skills training is needed in the implementation of E-Governance; c) There is a need for training on excellent service so that they know how to behave well and appropriately to maximize service to the community